2009
DOI: 10.1016/j.geomorph.2008.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from field-based studies of rates of soil erosion on degraded land in the central Karoo, South Africa

Abstract: The goal of the research is to develop components of the method aimed at output of information on reliefforming processes from archival and current remote sensing (RS) data with the use of the latest dataprocessing technologies, inclu ding photogrammetry and geoinformation systems (GIS). The proposed components of the methods are highly informative and economically effective. The object under study is located at the border of two active tectonic structures, the South Tatar arch and Melekesskian depression in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…Recent research in South Africa's semi-arid Karoo badlands region has shown that channel erosion in colluvium behaves in a "cut-and-fill" manner in that the measured erosion is small, but the quantity of material moved through the channel is nearly an order of magnitude greater than the measured erosion because sediment is eroded and redeposited in successive events (Keay-Bright and Boardman, 2009). Moreover, within a gully system there is significant contribution of sediment from sidewalls and interfluve/interrill areas.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent research in South Africa's semi-arid Karoo badlands region has shown that channel erosion in colluvium behaves in a "cut-and-fill" manner in that the measured erosion is small, but the quantity of material moved through the channel is nearly an order of magnitude greater than the measured erosion because sediment is eroded and redeposited in successive events (Keay-Bright and Boardman, 2009). Moreover, within a gully system there is significant contribution of sediment from sidewalls and interfluve/interrill areas.…”
Section: Introductionmentioning
confidence: 97%
“…A few studies have investigated the relationship between precipitation intensity and soil erosion at the plot scale under natural precipitation conditions over several years (Baartman et al, 2012;Keay-Bright and Boardman, 2009;Porto et al, 2014;Wei et al, 2010). Capra et al (2009) investigated the relationship between gully erosion and the precipitation erosivity factor in a cultivated catchment in Italy at a yearly scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are described as lithosols (shallow soils on hard or weathered rock (SANBI, 2012). This is particularly true of badlands and heavily degraded areas where surfaces are compact: bulk densities 1.6-1.9 g cm 3 with mean organic matter content of 2.4% (Keay-Bright and Boardman, 2009;Dickie and Parsons, 2012). Mean particle size for 10 badland sites (< 2mm) is reported as 7% clay, 66% silt and 27% sand using a Malvern laser-granulometer with Hydro-2000 dispersal unit .…”
Section: The Study Areamentioning
confidence: 99%
“…However, most material eroded by humans is not delivered to the oceans, but is deposited within catchments if the carrying capacity of rivers is exceeded. Thus, local soil erosion rates may be an order of magnitude greater than the net sediment yield to the oceans (Martin, 1987;Garland et al, 1999;Wilkinson and McElroy, 2007;Keay-Bright and Boardman, 2009). …”
Section: Introductionmentioning
confidence: 99%